ANALISIS FLUKTUASI HARGA SAHAM BLUE CHIPS DENGAN MENGGUNAKAN ALGORITMA C4.5 - Yohanes Leonardus Dwi Pradipta; Desi Arisandi; Tri Sutrisno (Jurnal Ilmu Komputer dan Sistem Informasi, 2022)
In this digital era, the development of stock investment has been fairly rapid and has begun to be used as a source of livelihood for some people, especially during the pandemic. However, for some people who are not familiar with stocks, they will find it difficult to make a decision to make transactions in the stock market. Because in the stock itself, there are several categories based on their quality, ability, and reliability in various situations. With this problem, a thesis was made with the title "Analysis of Blue chip Stock Price Fluctuations Using the C4.5 Algorithm." This thesis uses stocks that are in the Blue Chip Stock category because these stocks are rated very well from all aspects and can be relied on, especially by people who are not very deep into trading in the stock world. From the existing problems, a program is needed to help people who want to make transactions by analyzing stock price fluctuations by studying their movements over a certain time span. In this program, blue chip stock data will be used, which was originally in the form of numerical data. The things that are included in the stock data are the prices of open, close, high, low, and the number of transaction volumes registered and taken from the Yahoo Finance Page. Then the stock data will be converted into data in the form of categories. This is a requirement for using the C4.5 method. The results issued from this program are in the form of stock price categories that go up, down, or even balanced. Program testing is carried out in five stages. The average accuracy that has been obtained from the five stages is 82.4%.